(untitled) - ASSEMBLY LANGUAGE LIBRARY (USA, 1993)
1.About this manual / 2.Spontaneous assembly for c/c++ / 3.Programming whit spontaneous assembly for c/c++ / 4.Porgramming whit inline assembly / 5.Array management / 6.Buffet manipulation / 7.Character classification and conversion / 8.Console I/O / 9.Data compression / 10.Data conversion / 11.Date and time manipulation / 12.DOS console I/O / 13.File and directory management / 14.File I/O / 15.Integer math / 16.Memory mangement / 17.Memory manipulation / 18.Memory models / 19.Miscellaneous DOS / 20.Miscellaneous Hardware / 21.Multitasking / 22.Program and environment control / 23.Quad class for C++ / 24.Scripted I/O / 25.Star/Exit / 26.String manipulation / 27.Table management / 28.TSRs and device drives / 29.Utility / 30.Virtual screen / 31.Windowing
Incluye indice analitico pag.879 / Apendice pag.849
Keywords: LENGUAJES DE PROGRAMACION - (C++)